Long-Term Clinical Performance of Aesthetic Restorations in Primary Molars: A Case Report - Luciana Pomarico; Beatriz Gonçalves Neves; Lucianne Cople Maia; Laura Guimarães Primo (Hindawi Limited, 2011)
There is a great diversity of restorative materials and techniques for deciduous molars with significant coronal destruction, including resin composite restorations and biologic restorations (portions of natural teeth). By using 4 evaluation methods, this study aimed at longitudinally evaluating the effectiveness of restorations in the deciduous molars of a patient having high caries activity, using adhesive techniques. The evaluation methods consisted of the fibre-optic transillumination method, clinical evaluation based on the United States Public Health Service criteria, radiographs, and an indirect method, scanning electron microscopy. Despite the patient's poor biofilm control, the restorative techniques were shown to be efficacious, particularly the biologic restorative technique.